Unsafe bicyclist overtaking behavior in a simulated driving task: The role of implicit and explicit attitudes. (September 2020) - Goddard, T.; McDonald, A.D.; Alambeigi, H.; Kim, A.J.; Anderson, B.A.
Highlights: The novel methodology linked 105 respondents' conscious and subconscious attitudes with a simulated driving task Nearly one-half of driving simulator participants "close passed" the bicyclist Negative attitudes toward bicyclists predicted passing distance, speed, and time-to-collision People with negative attitudes about bicyclists as legitimate roadway users had a higher maximum speed while passing Self-identified cyclists passed at higher speeds, while people who bicycle at least weekly passed closer but more slowly Abstract: There is extensive literature into the mechanisms of injury in traffic crashes involving vulnerable road users (VRUs), but little research into the social or psychological factors in causation in these crash types. Attitudes and emotional associations can affect how people attend to objects in their visual environment and physical approach/avoidance responses, but few studies have extended these approaches into the road safety domain. Existing driving simulator studies of driver-bicyclist interactions have focused on driver behavior but not underlying attitudes and their effect on safety-related behaviors. This research explored the impact of implicit and explicit attitudes on drivers' behavior in interactions with bicyclists. In a driving simulator, various objective measures of safety (e.g., speed, passing distance, crash occurrence) were collected in an overtaking scenario. Participants' self-reported attitudes about driving and bicyclists were collected via survey instrument, along with an online test of subconscious attitudes called an Implicit Association Test, developed to examine preference between drivers and bicyclists. Importantly, this study examined not only distance, but duration and speed during overtaking. Results demonstrate that conscious attitudes affect how quickly and closely drivers overtake bicyclists. Participants who hold negative attitudes about bicyclists as a legitimate road user group passed significantly faster, while people with concerns about their knowledge or judgment about overtaking a bicyclist passed further and more slowly. Drivers self-identification as a bicyclist predicted higher passing speeds, while respondents who bicycle weekly drove closer but more slowly to the simulated bicyclist. These behaviors did not significantly differ based on the measure of implicit attitudes. The results of this study provide potential avenues for infrastructure and education interventions to improve pedestrian and bicyclist safety. Additionally, pairing driving simulator behavior with attitudinal measures represents a significant methodological contribution.